Serious games for carpal tunnel syndrome (CTS) rehabilitation treatment - Yuzawani, Yusoff (2019)
Carpal Tunnel Syndrome (CTS) is a medical condition due to median nerve compression when traveling through the carpal tunnel's wrist. The carpal tunnel is a narrow passage in the bracelet that opens in the hand. It is surrounded by the below wrist bones and the transverse carpal ligament above. The middle nerve runs through the carpal tunnel and gives the thumb, forefinger, middle finger and half of the ring finger. Many tendons also pass through this carpal tunnel and the large median nerve can be easily compressed if swelling occurs, causing carpal tunnel syndrome. Physical therapy and surgery are two wishes for rehabilitation for CTS. Serious games for carpal tunnel syndrome (CTS) rehabilitation treatment develop for help and benefits the patient with Carpal Tunnel Syndrome. This game develop by following physiotherapy movement for the game and all the element and requirement in this game from medical rehab so that it more effective to user. This game make patient feel fun to do the exercise. The ADDIE methodology model is chosen because it provides a systematic structure while this game is developing. This model has five phases to develop which are the analysis, design, development, and implementation and evaluation system. Serious games for carpal tunnel syndrome (CTS) rehabilitation treatment consist of two main major including game and about CTS. Game for CTS patient develop by following physiotherapy movement and it consist of two movement which is active range of motion and wrist extension and each movement have two level, for each level have difference pattern of game for user to complete. In addition, about CTS consist of information about CTS, symptoms of CTS, treatment and exercise for user to refer. Serious games for Carpal Tunnel Syndrome (CTS) Rehabilitation Treatment has been test by patients and Mr. Azeri as a medical rehab at Pusat Kesihatan Pelajar, UMP Gambang test the effectiveness this game to the patient. This test helps to achieve this game's goal. This game helps and benefits the carpal tunnel syndrome patient so that pain can be reduced and CTS avoided. According to the testing it help patient to relief their pain by play CTS game and give them more information about CTS.